The Will with Notary Deed in Efforts to Apply the Principles of Justice from the Perspective of Islamic Law and Civil Law - Yulies Tiena Masriani; Ridho Pakina (International Journal of Educational Research & Social Sciences, 2022)
A will is a part of human life related to a person's message regarding the gift of the property after death. The existence of problems with wills made orally causes issues in the family. In granting this will, several requirements must be completed so that the wills do not cause problems in the future. The normative juridical research approach, descriptive-analytical research specifications, data collection through secondary data in the form of library research and documentation studies, and qualitative analysis methods. The study results found that the will was made with a notary deed to ensure legal certainty. In applying the principle of justice, it is necessary to limit the granting of wills, from the perspective of the Islamic law that a will is only allowed a maximum of 1/3 of the entire inheritance. Meanwhile, in the perspective of civil law, granting wills must pay attention to the provisions of the Legitieme Portie or the share of property that must be given to the heirs in a straight line to create justice for the heirs.